Війна і млин: особливості ведення млинарського господарства у Львові в другій половині XVII cт. - Погорілко, М. Я. (НТУ "ХПІ", 2014)
Пропонується аналіз особливостей ведення млинарського господарства у Львові в другій половині XVII – на початку XVІІІ ст., здійснений на основі понад 150 договорів оренди. Договори оренди підписували господар-орендар та місто-власник. У них зазвичай детально фіксувалися умови та застереження щодо поводження з млином, яке могло зумовити його занепад. Цей відрізок часу є надзвичайно важливим, адже постійні військові облоги підкосили економічний розвиток міста та околиць і фактично призвели до занепаду міста.

In this article we offer an analysis of the peculiarities of city economy in example of mill in Lviv in the second half of the 17th – early 18th century. It is based on more than 150 lease agreements of that period between city administration and renters. The lease agreements were signed by the tenant, and the city is the owner. They usually detail was recorded conditions, and warnings regarding the treatment of the mill, which could lead to its decline. This period is extremely important for the history of Lviv, because the constant attacks on Lviv crippled economic development of the city and its suburbs, and, in fact, led to the decline of the city, which can be seen during the XVIII c.
A war and a mill: mill economy of Lviv in the second half of the 17th – early 18th century
Keywords: Україна історія; Львів історія; міське господарство; млинарство; water mills; Lviv; city economy; siege of the city